Losartan Has a Comparable Effect to Human Recombinant ACE2 in Reducing Interleukin-6 (IL-6) Levels on Human Adipocytes Exposed to SARS-CoV-2 Spike Protein - Hanestya Oky Hermawan; Meity Ardiana; I Gde Rurus Suryawan; Primasitha Maharany Harsoyo; Muhammad Rafli (The Indonesian Biomedical Journal, 2023)
BACKGROUND: High angiotensin-converting enzyme 2 (ACE2) expression in adipocyte cells facilitates the initiation of SARS-CoV-2 infection and triggers a cytokine storm. This finding suggests that obesity is an independent risk factor for the severity of the symptoms caused by COVID-19. The use of cardiovascular medications that focus on ACE2, such as angiotensin II receptor blockers, remains controversial, and their effects on inflammatory cytokine production and ACE2 expression in cells, especially adipocytes, remain inconsistent.METHODS: The human adipocytes were isolated from obese donor subcutaneous adipose tissue and infected with the subunit S1 spike protein from SARS-Cov-2. The adipocytes were later treated with either hrsACE2 or losartan. The levels of ACE2 and inflammatory cytokines interleukin (IL)-6, IL-1β, and tumor necrosis factor (TNF)-α were measured using enzyme linked immunosorbent assay (ELISA). ACE2 and S1 spike protein binding assays were also performed. RESULTS: ACE2, IL-6, and TNF-α levels were significantly increased in human adipocyte cells infected with SARS-Cov-2 but not IL-1β. There was a statistically significant positive correlation between ACE2 and IL-6 (r=0.878, p<0.001). Administration of losartan and hrsACE2 was shown to reduce ACE2 levels and its binding to the SARS-CoV-2 S1 spike protein, and IL-6 levels were statistically significant, but had no significant effect on IL-1β or TNF-α levels.CONCLUSION: This study shows that the administration of losartan in COVID-19 may not be harmful, but instead has a protective effect similar to that of hrsACE2 in preventing a cytokine storm, especially IL-6.KEYWORDS: obesity, SARS-CoV-2, losartan, IL-6, ACE2